ANALISIS PREDIKSI KEPAILITAN BANK KESAWAN (Studi Atas Laporan Keuangan Bank 1998 -2009) - Devi Rosinta (JURNAL LENTERA BISNIS, 2017)
The purpose of research (1) To determine the Bank Kesawan bankruptcy prediction model based on financial statements of the bank concerned, and (2) To determine the formation of the Bank's bankruptcy prediction model Kesawan. Methodology research using quantitative, with an observed variable is Loans to Capital (X1), Fixed assets to Equity (X2), Fixed assets to Capital (X3) and Return on Capital (X4), and the dependent variable in this study is Zscore, techniques data analysis using correlation test, regression testing and test hypotheses.The results of the data variable Loans to capital, fixed assets to equity, Fixed asset to capital and return on capital simultaneously with correlation  value of 0422 or 42.2% so there is a strong positive relationship regression test results Z = 47.881 to 1.642 +1.084 X4 -0.508 -0.018 X5 X6 X10, From the test results shows that the Z value of 48.96 is thus variable variable (Loans to capital, fixed assets to equity, Fixed asset to capital and return on capital) does not put pressure on banks bankruptcy Kesawan, results of hypothesis testing Fcont 5.435> 4.140 Ftable where r = 0026 <a = 0.05 thus independent variables (Loans to capital, fixed assets to equity, Fixed asset to capital and return on capital) can be used as benchmarks to know the symptoms of bankruptcy on the bank Kesawan for 10-year observation period.Keyword: Prediction of Bankruptcy, Financial Report